Teaching the Use of Respiratory Inhalers to Hospitalized Patients with Asthma or COPD: a Randomized Trial - Press, Valerie G. (Springer-Verlag, 2012)
BACKGROUND: Hospitalized patients frequently misuse their respiratory inhalers, yet it is unclear what the most effective hospital-based educational intervention is for this population. OBJECTIVE: To compare two strategies for teaching inhaler use to hospitalized patients with asthma or chronic obstructive pulmonary disease (COPD). DESIGN: A Phase-II randomized controlled clinical trial enrolled hospitalized adults with physician diagnosed asthma or COPD. PARTICIPANTS: Hospitalized adults (age 18 years or older) with asthma or COPD. INTERVENTIONS: Participants were randomized to brief intervention [BI]: single-set of verbal and written step-by-step instructions, or, teach-to-goal [TTG]: BI plus repeated demonstrations of inhaler use and participant comprehension assessments (teach-back). MAIN MEASURES: The primary outcome was metered-dose inhaler (MDI) misuse post-intervention (<75% steps correct). Secondary outcomes included Diskus® misuse, self-reported inhaler technique confidence and prevalence of 30-day health-related events. KEY RESULTS: Of 80 eligible participants, fifty (63%) were enrolled (BI n = 26, TTG n = 24). While the majority of participants reported being confident with their inhaler technique (MDI 70%, Diskus® 94%), most misused their inhalers pre-intervention (MDI 62%, Diskus® 78%). Post-intervention MDI misuse was significantly lower after TTG vs. BI (12.5 vs. 46%, p = 0.01). The results for Diskus® were similar and approached significance (25 vs. 80%, p = 0.05). Participants with 30-day acute health-related events were less common in the group receiving TTG vs. BI (1 vs. 8, p = 0.02). CONCLUSIONS: TTG appears to be more effective compared with BI. Patients over-estimate their inhaler technique, emphasizing the need for hospital-based interventions to correct inhaler misuse. Although TTG was associated with fewer post-hospitalization health-related events, larger, multi-centered studies are needed to evaluate the durability and clinical outcomes associated with this hospital-based education.